Improving Digital Literacy on Business for Adolescents in SMP Muhammadiyah Daarul Arqom Klaten - Nurjanah, Hidayatul; Asiyah, Nur; Umam, Robith Khoiril; Rizal, Muhammad (LPPM UNIVERSITAS DIAN NUSWANTORO, 2023)
This community service (PKM) objectives are to discover how these adolescents utilize digital platforms and their obstacles for their businesses and to find out how to improve digital literacy on business for adolescents in SMP Muhammadiyah Daarul Arqom Klaten . This activity employs qualitative research using four steps in collecting the data; observation and interview, preparation of material, implementation of activities, and evaluation. This community service (PKM) was held from March 11-13, 2023 in SMP Muhammadiyah Daarul Arqom Klaten with the total of 40 adolescent participants. The first result, the majority students use internet and social media for entertainment and pleasure, not business interest. Second, the students faced obstacles in improving digital literacy and starting business using digital media. Third, the community service (PKM) team create solution to improve digital literacy on business for adolescent such as increasing the knowledge of digital literacy and its utilization, arranging schedules for individual target or business, learning more about the product strategy and marketing, upgrading and escalating new information every day, finding networks to level up their spread of communication, and being confident and independent, especially on financial life.